PELAKSANAAN FUNGSI PARTAI POLITIK DI WILAYAH KOTA PEKANBARU DALAM MENYERAP, MENGHIMPUN DAN MENYALURKAN ASPIRASI POLITIK MASYARAKAT BERDASARKAN UNDANG-UNDANG NOMOR 2TAHUN 2011 TENTANG PERUBAHAN ATASUNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK - Rofika Shopia; Dodi Haryono; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Law Of Republic Indonesia Number 2 Year 2009 concerning the changing Law Of Republic Indonesia Number 2 Year 2008 concerning Political Party which ruled political party as democratic based to run its function as absorber, collector, and people aspiration distributor that should be done continuously by political party members. But in fact, political party in this case, its function only has been done bt members who want to be legislative candidates or executive candidates in election. Based on this issue, problem identification in this thesis, are: first, how do political party mechanism in absorbing, collecting, and distributing people aspiration? Second, did it run well? Third, what are the challenges and effort which are done by political party in absorbing, collecting, and distributing people aspiration, and also its problem solving to solve the challenges?This research is sociological law research and descriptive. This research was located in Region Representative Committee Office Of Golongan Karya Party in Pekanbaru, Branch Representative Committee Office Of Demokrasi Indonesia Perjuangan Party in Pekanbaru, and Region Representative Committee Office Of Amanat Nasional Party. The data which is used consist primary data and secondary data. Technically data was collected by field study (interview and questions and library study). Then analized qualitatively and make conclusion by deductive thought method.Based on this research , as results we know that absorbing , collection mechanism, and distribution of people aspiration has no specific rule sin those parties especially about the mechanism so parties can make their own conclusion about people needs, political party still not optimum or maximumin doing their functions in absorbing, collecting, and distributing people aspiration. There are many challenges such as party’s member have less participation, people society have less participation, the improvement of negative thinking or mind around the people and limited resources. The solution is by making a value system and sanction to members , build a good relationship with NGO, enlighment society mind, and find another source which has no boundaries.Key Word : political party – aspiration - society